Degassing binder on Resonant Acoustic Mixer - Gill, Philip (Cranfield University, 2018)
TYPE-I.avi: High speed video of degassing binder on Resonant Acoustic Mixer.
Keywords: 'resonant acoustic mixing'; 'EOE'; 'Chemical Engineering not elsewhere classified'; 'Manufacturing Engineering not elsewhere classified'; 'Powder and Particle Technology'; 'Process Control and Simulation'